2021
DOI: 10.3390/en14238146
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Radar Speed Cameras and Panels Indicating the Vehicles’ Speed as Traffic Calming Measures (TCM) in Short Length Urban Areas Located along Rural Roads

Abstract: Traffic calming measures (TCMs) are implemented in urban areas to reduce vehicles’ speed and, generally speaking, results are obtained. However, speed is still a problem in rural roads crossing small villages without a bypass and with short-length urban areas, since drivers do not normally reduce their speed for that short segment. Hence, various TCM can be installed. It is necessary to maintain a calm area in these short segments to improve road safety, especially for pedestrian aiming to cross the road, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Similar studies previously have investigated the influential roadside factors of speeding behavior. An example of these tools is traffic calming measures, which are traffic lights turning red in case of exceeding speed limits by drivers and are used mostly in rural or intercity roads rather than in urban areas to reduce the risk of RTIs in areas with lower existence of traffic lights ( 40 ). It has been shown that the appropriate placement of these tools could prevent excess driving speeds and improve pedestrians' safety passing the roads ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies previously have investigated the influential roadside factors of speeding behavior. An example of these tools is traffic calming measures, which are traffic lights turning red in case of exceeding speed limits by drivers and are used mostly in rural or intercity roads rather than in urban areas to reduce the risk of RTIs in areas with lower existence of traffic lights ( 40 ). It has been shown that the appropriate placement of these tools could prevent excess driving speeds and improve pedestrians' safety passing the roads ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…An example of these tools is traffic calming measures, which are traffic lights turning red in case of exceeding speed limits by drivers and are used mostly in rural or intercity roads rather than in urban areas to reduce the risk of RTIs in areas with lower existence of traffic lights ( 40 ). It has been shown that the appropriate placement of these tools could prevent excess driving speeds and improve pedestrians' safety passing the roads ( 40 , 41 ). Considering the importance of pedestrian safety strategies and the pedestrian fatality risk in high-speed driving roads ( 42 ), borrowing the experience of these studies could help in controlling the KD challenge.…”
Section: Discussionmentioning
confidence: 99%
“…While traffic-calming measures (TCMs) have been in place for several years, they have gained renewed attention as a successful strategy to address the evolving challenges of energy-efficient and smart cities. Numerous studies have emphasized the potential benefits of TCMs in mitigating the adverse impacts of motorized traffic on urban centers, ultimately enhancing general traffic conditions and the overall well-being of citizens [3,11,[57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…The modeling of highway traffic is one of the most important activities for researchers and specialists in the field of transport. This activity helps to understand the process, the importance of data used in the model and the influence over the results [1,2]. The impact assessment for the influence of endogenous and exogenous random events with consequences for users provides the transport infrastructure administration the opportunity to implement a new system based on smart equipment for traffic monitoring and control [3].…”
Section: Literature Reviewmentioning
confidence: 99%